Updated Insights on Cardiac and Vascular Risks of Proton Pump Inhibitors: A Real-World Pharmacovigilance Study - Zhai, Yinghong; Ye, Xiaofei; Hu, Fangyuan; Xu, Jinfang; Guo, Xiaojing; Lin, Zhen; Zhou, Xiang; Guo, Zhijian; Cao, Yang; He, Jia (Frontiers in Cardiovascular Medicine, 2022)
Background: Proton pump inhibitors (PPIs) are among the most widely prescribed medications in clinical practice. However, there are also concerns about the potential risks of long-term PPI use. The present study aimed to examine the safety of PPIs and summarize their potential cardiac and vascular risks in a real-world setting. Methods: This pharmacovigilance study extracted records between January 2015 and December 2019 from the FDA Adverse Event Reporting System (FAERS) database. The association of seven PPI medications with cardiac and vascular events (CVEs) were evaluated. Two established pharmacovigilance methods, reporting odds ratio (ROR) and information components (IC) based statistical shrinkage, were used to measure disproportionality. Results: In total 62,140 CVE records associated with PPI use were investigated. Women showed a higher proportion (54.37%) of PPI-associated CVEs. The median time from PPI initiation to CVE onset was 97 (interquartile range (IQR): 8-491) days, with the shortest median time of 42 days (IQR: 2-277 days) for esomeprazole, and the longest time of 389 days (IQR: 0-525 days) for dexlansoprazole. Although PPIs were not associated with elevated CVE risks compared those of the whole database (IC025/ROR025=-0.39/0.74), various signals emerged. Despite some similarities exist between the PPIs, their cardiac and vascular safety profiles varied significantly. Pantoprazole showed the broadest spectrum of signals, from thrombotic thrombocytopenic purpura (IC025/ROR025=0.01/1.08) to renal haemangioma (IC025/ROR025=3.14/9.58). Esomeprazole showed the second-broadest spectrum of toxicities, ranging from duodenal ulcer haemorrhage (IC025/ROR025=0.07/1.28) to hypertensive nephropathy (IC025/ROR025=4.09/18.72). Vascular signals were more dominant than cardiac signals, suggesting that vascular function was more heavily affected. Hypertensive nephropathy, renal haemangioma, renal artery stenosis, and renal infarct had strong signals across most PPI regimens and merited further attention. Conclusions: PPIs may inflict various CVEs, particularly those involving the vascular system, on the users. Given the wide range of onset times and different toxicity profiles for various PPI medications, they should be prescribed with caution.